1998
DOI: 10.4098/at.arch.98-51
|View full text |Cite
|
Sign up to set email alerts
|

Speed and actual distances travelled by radiocollared wolves in Białowieża Primeval Forest (Poland)

Abstract: Marco MUSIANI1, Henryk OKARMA2 and Włodzimierz JĘDRZEJEWSKI3 M usiani M., Okarma H. and Jędrzejewski W. 1998. Speed and actual distances travelled by radiocollared w olves in Białowieża Primeval Forest (Poland). Acta Theriologica 43: 409-416.The relationship between the straight line distances (SLD), obtained from tele metry locations, and actual distances travelled by wolves Canis lupus (ADT), measured by snowtracking, was investigated in Białowieża Primeval Forest, E Poland, in winter 1995/96. Radiolocations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 42 publications
3
46
1
Order By: Relevance
“…We found that Wolves travelled a median distance of 0.08 km/hr, which is substantially lower than that reported for Wolves travelling in the forest during winter (1.6-6.1 km/hr) (Musiani et al 1998), on iced surfaces (8 km/hr) (Mech 1966), and on tundra during summer (8.7 km/hr) (Mech 1994). This difference could be largely due to the advantages of continuous (hourly) GPS monitoring in this study.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…We found that Wolves travelled a median distance of 0.08 km/hr, which is substantially lower than that reported for Wolves travelling in the forest during winter (1.6-6.1 km/hr) (Musiani et al 1998), on iced surfaces (8 km/hr) (Mech 1966), and on tundra during summer (8.7 km/hr) (Mech 1994). This difference could be largely due to the advantages of continuous (hourly) GPS monitoring in this study.…”
Section: Discussioncontrasting
confidence: 79%
“…Further, by combining GPS radio-collar technology with traditional methods used to study wolf kill rates (Mech 1974), a more comprehensive representation of wolf travel rates was established. Results from this approach found a clear difference in Wolf travel rates related to ungulate kill sites, which is consistent with both anecdotal information and other research (Mech 1966;Peterson 1977;Hayes et al 2000).We found that Wolves travelled a median distance of 0.08 km/hr, which is substantially lower than that reported for Wolves travelling in the forest during winter (1.6-6.1 km/hr) (Musiani et al 1998), on iced surfaces (8 km/hr) (Mech 1966), and on tundra during summer (8.7 km/hr) (Mech 1994). This difference could be largely due to the advantages of continuous (hourly) GPS monitoring in this study.…”
supporting
confidence: 90%
“…That value is based on assumptions of linear movement between position fixes. Results from other species (Musiani et al, 1998;Rowcliffe at al., 2012), including another mustelid, the fisher [Martes pennanti (Powell, 1979)], indicate that radiotracking underestimates real movement distances by 30-90%. Assuming a correction factor of 50% (Powell, 1979), our free-living weasels traveled 2.2kmday -1 , quite similar to the 1.94kmday -1 of wheel-running we observed in captive weasels.…”
Section: Running Behaviormentioning
confidence: 99%
“…Consistent with wolf movement in other areas, they selected low use trails (Thurber et al 1994) likely because they offered easy travel routes across the study area with low probabilities of encountering people (Musiani et al 1998, James and Stuart-Smith 2000, Callaghan 2002, Whittington et al 2005, Hebblewhite 2006). Conversely, the wolves avoided areas near the resort and weakly avoided trails with high levels of human use, presumably to minimize the probability of encountering people (Thurber et al 1994, Theuerkauf et al 2003a, Whittington et al 2005.…”
Section: Resources Important To Wolves and Change In Resource Usementioning
confidence: 99%